THU0395 Zoledronic Acid: Patterns of Prescription and Side Effects in 204 Patients. (23rd January 2014) - Grados, D.; Martínez-Morillo, M.; Erra, A.; Holgado, S.; Tejera, B.; Riveros, A.; Tena, X.; Rotés, I.
Abstract : Background: Zoledronic acid is an intravenous bisphosphonate used in osteoporosis and Paget's disease of bone. It is usually well tolerated, although it may cause some side effects. Objectives: To describe the clinical characteristics, indications, side effects and densitometric parameters in patients treated with zoledronic acid. Methods: Retrospective study (2006-2012) at two hospitals with a referral area of 900.000 people. We reviewed the medical records of patients treated with zoledronic acid. We collected the epidemiological and clinical features and side effects. We conducted a telephone interview to complete the missed data. Results: Two hundred and four patients received zoledronic acid: 146 women (71.6%) and 58 men (28.4%), with mean age of 70.5 years (range: 38-89 years). The medical indication for the administration was: 149 osteoporosis, 46 Paget's disease of bone and 8 other bone diseases (5 SAPHO syndrome, 2 Brittle bone's disease and 1 progressive multifocal osteitis). The causes of osteoporosis were: postmenopausal 93 (62.4%), secondary 42 (28.2%) - most of them due to glucocorticoid treatment -, and male osteoporosis 14 (9.4%). Seventy-three percent of the patients with osteoporosis had received other treatments previously (73.6% oral bisphosphonates, 27.3% teriparatide or PTH 1-84, 22.7% intravenous ibandronate, 18.1% strontium ranelate, 10% calcitonin, 9% raloxifene and 7.3% pamidronate). Ninety-seven patients (65.1%) had fractures before treatment: vertebral (82%), rib (12.3%), wrist (9.2%), femur (8.2%), other (12.3%) - isquiopubian branches, foot, elbow, humerus, phalanges. Only 14 patients (9.4%) had fractures after treatment. The average of bone mineral density before treatment was: T score -3.1 in the lumbar spine (L2-L4) and -2.4 in the femur. Of all patients, 110 (73.8%) had received a single infusion, 46 (30.9%) 2 infusions, 38 (25.5%) 3 infusions and 10 (6.7%) 4 infusions of zoledronic acid. Thirty-nine patients had side effects (19.1%): 26 men and 13 women, with a mean age of 66.4 years. Twenty-three of these patients were treated because of having osteoporosis, 15 Paget's disease of bone and one osteogenesis imperfecta. The most described side effects were: flu-like syndrome (69%), arthralgia (7.7%), uveitis (5.1%) and arthritis, kidney failure, hypertensive crisis, rash, epistaxis, fatigue and ventricular arrhythmia (2.6 % each). We used chi-square test with Yates correction to compare the incidence of side effects in patients with osteoporosis to patients with Paget's disease of bone. We obtained a value of 5.56 with statistical significance (p = 0.01) for Paget's disease of bone. Conclusions: The most common indication for administration of intravenous zoledronic acid is postmenopausal osteoporosis. A high percentage of patients had previously received different treatments and had fractures before treatment. Nearly 20% of patients have side effects and the most common is a flu-like syndrome. Patients treated for Paget's disease of bone have a higher incidence of side effects than those treated for osteoporosis (p = 0.01). Disclosure of Interest: None Declared